The Tragedy of Divided Christianity: Diagnosis of Main Problems on the Basis of the "Vota" Sent to the Second Vatican Council - Wąsek, Damian; Gilski, Marek (Verbum Vitae, 2025)
This article addresses diagnosing problems emerging from the existing divisions among Christians. The analysis is based on the vota submitted in the preparations for the Second Vatican Council. The voices of bishops, major religious superiors, and Catholic universities reveal four areas where a lack of Christian unity has disastrous consequences. The first area is sociopolitical and shows the problem of marginalization of Christianity, which cannot respond to the challenges the modern world faces. The second area concerns Christ’s prayer for his disciples to be one, presenting Christianity as failing to fulfill the Savior’s desires. The third, concerning the missionary and apologetic activity of the Church, reveals the incredibility and weakness of divided Christianity. The fourth, presenting the issues of interdenominational marriages, shows the consequences of an overly legalistic approach to sacramental reality. The final part includes conclusions and perspectives emerging from the analyses.